2017
DOI: 10.1016/j.conb.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

From the statistics of connectivity to the statistics of spike times in neuronal networks

Abstract: An essential step toward understanding neural circuits is linking their structure and their dynamics. In general, this relationship can be almost arbitrarily complex. Recent theoretical work has, however, begun to identify some broad principles underlying collective spiking activity in neural circuits. The first is that local features of network connectivity can be surprisingly effective in predicting global statistics of activity across a network. The second is that, for the important case of large networks w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 99 publications
0
63
0
Order By: Relevance
“…To understand the emergence of such non-random connectivity, a growing body of theoretical and computa-24 tional work has been developed to link connectivity architecture to the coordinated spiking activity of neurons, 25 especially in recurrent networks [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. These studies can be divided into two classes: those that examine the 26 influence of externally structured input on activity-dependent refinement [42][43][44][45], and those that investigate the 27 autonomous emergence of non-random connectivity in the absence of patterned external input, purely driven by 28 emergent network interactions [5,6,46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the emergence of such non-random connectivity, a growing body of theoretical and computa-24 tional work has been developed to link connectivity architecture to the coordinated spiking activity of neurons, 25 especially in recurrent networks [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. These studies can be divided into two classes: those that examine the 26 influence of externally structured input on activity-dependent refinement [42][43][44][45], and those that investigate the 27 autonomous emergence of non-random connectivity in the absence of patterned external input, purely driven by 28 emergent network interactions [5,6,46].…”
mentioning
confidence: 99%
“…We write the pairwise covariance as a sum of the internal correlation and a novel term that conveys the 370 external structured activity as common input [40]:…”
mentioning
confidence: 99%
“…390 The necessity of higher-order patterns for stable activity has strong implications for 391 neural coding. Previous work has already demonstrated that correlations enhance 392 coding, with triplet correlations having an advantage over pairwise 393 [5,16,18,[21][22][23][52][53][54]. The neural code must rest upon a foundation of stable 394 propagation of spikes, which we have shown in turn rests on higher-order motifs and 395 coordinated integration.…”
mentioning
confidence: 77%
“…Several related studies have focused on a theoretical link between network structure and correlated spiking activity recorded from a large number of neurons, without attempting to explicitly estimate synaptic connections (see [88][89][90][91][92][93][94] and [95] for review). Of major relevance in this regard is the extent to which effective interactions among observed neurons are reshaped by coupling to unobserved neurons [83,96].…”
Section: Estimation Of Synaptic Couplingmentioning
confidence: 99%